Efektivitas Penggunaan Media Pembelajaran VIdeoscribe Untuk Meningkatkan Motivasi Belajar dan Hasil Belajar Mahasiswa - Nugraha, Derry; Rahayu, Ludia Sri; Berliana, Berliana (Jurnal Ilmu Pendidikan, 2024)
This study aims to examine the effectiveness of using VideoScribe learning media in improving student motivation and learning outcomes. VideoScribe is a software that allows the creation of interesting and interactive whiteboard animation videos. The research method used is descriptive quantitative. The research sample was 100 student respondents of Linggabuana PGRI University SUkabumi. The research instrument is through a questionnaire in the form of a google form consisting The results showed that 70% of students were female. The validity test results show r table> r count, which is 0.195, so the question is asked valid. The reliability test result is 0.880> 0.60, so it is declared reliable. The test results are F count 25.539> F table 1.664, meaning that learning media and learning motivation have an effect on learning outcomes. The results of the T test partially affect learning outcomes because the results of T count are 2.586> 1.664. The implication of this research is the importance of integrating multimedia technology such as VideoScribe in learning to create a more interesting and effective learning environment for students.